MODAL SOSIAL KELUARGA BEDA AGAMA (Studi Sosiologis Tentang Relasi Pergaulan Anak dari Pasangan Beda Agama di Salatiga) - Erna Kurniawati N.M.A.S; Elly Esra Kudubun (Universitas Kristen Satya Wacana, 2015)
Children who tend to pick and choose friends even discriminate based on race, social level, or religion because there is discomfort felt by the difference. All that can arise due to the effects of the influence of parenting parents in educating , even overly restrictive attitude of parents their children so that the children difficult to associate with the outside world . In this study focused on how the parents of this form of interfaith couples and families build social capital such as trust, norms and networks, then applied to the child as a provision in the child to relate socially. This study is a descriptive study with a qualitative approach. Sources of data obtained interviews with informants or sources of interfaith couples, children of interfaith couples and their peers relations of children of interfaith couples. Data collection using secondary data in the form of complementary data related documents and regulations related to the problem under study. Data analysis techniques using data reduction, data display, and data verification. Social capital is the result of negotiations that formed the differences, one of which is the difference of religion. The results of these negotiations are formed in feeling comfortable with each other, love each other, love each other, expectations, take risks to achieve common goals, and tolerance. Religious differences in a family that is not a problem, but the difference was actually accepted as a reality of life to be thankful for, and helped shape the attitudes and behavior of children in the neighborhood association, which become more tolerant of differences, attitudes budge to reduce conflicts at the same time not obtrude one another , trusting and trustworthy.. Keywords : social capital , trust , norms , networks , family , social relationships of children.